Extraintestinal Manifestations of Coeliac Disease - Sanders, David (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Coeliac Disease (CD) affects at least 1% of the population. “Classical” CD refers to gastrointestinal presentations with anaemia and gastrointestinal symptoms. CD can, however, present with extraintestinal manifestations, the commonest of which are dermatitis herpetiformis and neurological presentations (e.g., ataxia, neuropathy, encephalopathy). Recognition and research into the pathophysiology of such manifestations is likely to enhance our understanding of this complex autoimmune disorder.